2001
DOI: 10.1063/1.1356039
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of LaCr1−xMxSb3 (M=V, Mn, Fe, Cu, and Al)

Abstract: The influence of Cr substitution by various metals (M=V, Mn, Fe, Cu and Al) on the magnetic state of the itinerant intermetallics La(Cr,M)Sb3 was studied by magnetization and magnetic susceptibility measurements up to 55 kG at 5 K and from 4.2 to 400 K, in a magnetic field of 1000 G, respectively. It was found that the Curie temperature (TC) and magnetization (M) of these compounds depend nonlinearly on the concentration, remaining in the vicinity of the values of TC and M measured for LaCrSb3. Curie temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…The family of compounds, RCrSb 3 (R = La-Nd, Sm, Gd-Dy), have had many investigations in the literature due to their unique magnetic and electrical transport properties [1][2][3][4][5][6][7][8][9][10][11][12]. The parent member in the series, LaCrSb 3 , has been studied in depth [3][4][5] because it has only one magnetic ion, Cr, yet it has a very complex magnetic phase diagram.…”
Section: Introductionmentioning
confidence: 99%
“…The family of compounds, RCrSb 3 (R = La-Nd, Sm, Gd-Dy), have had many investigations in the literature due to their unique magnetic and electrical transport properties [1][2][3][4][5][6][7][8][9][10][11][12]. The parent member in the series, LaCrSb 3 , has been studied in depth [3][4][5] because it has only one magnetic ion, Cr, yet it has a very complex magnetic phase diagram.…”
Section: Introductionmentioning
confidence: 99%
“…Systems containing a late transition metal have been the focus of most previous studies, whereas those containing an early transition metal remain poorly investigated. When M is a group 4, 5, or 6 element, the only compounds known so far are RE 3 MSb 5 (M ¼ Ti, Zr, Hf, Nb) [2][3][4][5], REMSb 3 (M ¼ V, Cr) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], and REZrSb [23][24][25][26]. In the Sb-rich phases, homoatomic Sb bonding networks are a recurring feature of the structures, in the form of one-dimensional chains in RE 3 MSb 5 or two-dimensional nets in REMSb 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on polycrystalline samples showed that V substitution does suppress the ferromagnetic transitions, and claimed that the mechanism of the ferromagnetic ordering can not be explained by a simple localized magnetic moment model [28]. Only the temperature dependence of magnetization was measured on the V-doped polycrystalline samples.…”
Section: Introductionmentioning
confidence: 99%